HARGA, KUALITAS PRODUK DAN MEREK TERHADAP KEPUTUSAN PEMBELIAN TAS KW CARTIER DI KALANGAN MAHASISWI SEBAGAI PENUNJANG PENAMPILAN KULIAH - Ahmad Adi Arifai; Zaleha Trihandayani (Universitas Indo Global Mandiri)
Price, product quality and brands purchase decision against kw cartier bags among students of Economics Faculty and Business University Muhammadiyah Palembang. The goal is to know whether there is influence of price, product quality and brand against purchasing decision kw cartier bags among students of Economics Faculty and Business University Muhammadiyah Palembang. The population in this study are female students of Economics Faculty and Business who use kw cartier bag whose number is unknown. samples taken 100 female students 2013/2014 using kw cartier bag with purvosive sampling technique. based on result of multiple linear regresi yield function Y = 3,960 + 0,367X1 + 0,210X2, it means that price and quality of product influence to purchase decision. test F with significant (0,000) and α (0.05) F count <Ftable then there is influence price, quality product and brand against purchase decision kw cartier bag. Test t with t arithmetic price of 3.814 and t table 1.985 tcount> ttable means there is influence of price against decision purchase kw cartier bag. t arithmetic product quality of 2.214 and t table 1.985 tcount> ttable means there is Influence of quality product against decision purchase kw cartier bag. t arithmetic brand of 0.778 and t table 1,985 t count <ttabel, meaning there is no influence on brand decision purchase kw cartier bag. determination test with a value of 24.5%, meaning that the purchase decision variable can be explained by the variable price and quality product of the remaining 24.5% is explained by other variables that are not examined.Keywords : Purchase decision, price, quality product and brand